The Relationship Between Burnout and Mental Health Towards Job Satisfaction Among First Responders - Sumitra Francis Thilagaratnam; Jasmine Adela Mutang (Psychology and Social Health Research Unit, 2023)
This cross-sectional study aims to examine the relationship between burnout, mental health, and job satisfaction among 180 first responders in Negeri Sembilan, Malaysia, with a particular focus on healthcare professionals. Participants were recruited through a snowball sampling method from government and private healthcare facilities across seven districts in Negeri Sembilan, Malaysia. Utilizing online surveys distributed through messaging platforms due to COVID-19 constraints, the study employed the Copenhagen Burnout Inventory (CBI), Depression, Anxiety, and Stress Scale (DASS-21), and Minnesota Satisfaction Questionnaire (MSQ) to collect data on burnout, mental health, and job satisfaction respectively. The results reveal significant negative correlations between burnout and job satisfaction, with personal and work-related burnout exhibiting significant associations. Mental health issues, including depression, anxiety, and stress, are found to be moderately negatively correlated with job satisfaction. The study underscores the need for targeted interventions to address these challenges and enhance the well-being and job satisfaction of first responders. Despite limitations in participant selection and sample size, the findings contribute valuable insights and underscore the importance of comprehensive strategies for the support and satisfaction of first responders in high-stress environments.